PERSEPSI MASYARAKAT TERHADAP LEMBAGA PENDIDIKAN ISLAM DI DESA PENGKOK KEDAWUNG SRAGEN JAWA TENGAH - Farah Muthia (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2019)
This research  used  descriptive-qualitative approach  with data  collection  techniquws in the  form of observation, interview and documentation. From the research  that has done,  the findings are as follows. First, people’s knowledge  of Islamic education and  Islamic educational is good  enough; seen  from many  positive responses of informant  who see the very impor- tant Islamic education and Islamic for them.  Second, by the attitude  of the society towards  the Islamic educational institutions, cognitively they have understood the importance of Islamic education and Islamic educational institutions, and affectively their response to the development of Islam is also quite good,  visible from the awareness to follow the study / assemblies  of existing science. Community behavior is getting better so that the number of criminals is reduced and public participation is increasing in religious activities held by religious leaders of Pengkok Village. Third, public interest in non-formal institutions Islamic education is very high; on the contrary,  the interest of the community towards the formal institution of Islamic education is still lacking. in demand due  to several factors in the fourth conclusion.  Fourth,  the lack of public interest  in the formal institutions  of Islamic Education is due  to the following factors. (1) educational background, (2) experience, (3) condition of institution,  (4) govern- ment policy, and (5) environment of institution management itself